Feeding difficulties in neonates following cardiac surgery: determinants of prolonged feeding-tube use. (23rd January 2017) - McKean, Elissa B.; Kasparian, Nadine A.; Batra, Shweta; Sholler, Gary F.; Winlaw, David S.; Dalby-Payne, Jacqueline
Abstract: Aim: The aims of this study were to examine the prevalence and potential correlates of feeding difficulties in infants who underwent cardiac surgery in the neonatal period and to investigate resource utilisation by infants with feeding difficulties. Methods: All neonates who underwent their first cardiac surgery at the Heart Centre for Children, The Children's Hospital at Westmead, between January and December, 2009 were included. Demographic, preoperative, intraoperative, and postoperative data were collected via electronic medical records. For the purpose of this study, feeding difficulty was defined as the requirement for ongoing tube feeding at the time of discharge home or transfer to another hospital. Results: Out of a total of 79 neonates, 24 (30%) were discharged home or transferred to another hospital with a feeding tube. Feeding difficulties were associated with the presence of a genetic syndrome (p<0.0001), assisted feeding preoperatively (odds ratio (OR)=4.4, p=0.03), and having a palliative procedure before biventricular repair (OR=5.1, p=0.02). Infants with feeding difficulties had significantly more reviews by speech pathologists ( M =5.9, SD=7.9), dieticians ( M =5.9, SD=5.4), and cardiac clinical nurse consultants ( M =1.2, SD=1.4) compared with those without feeding difficulties. Conclusions: This study identified factors that can be used in the early recognition of infant feeding difficulties, to help guide the direction of limited health resources, as well as being focal points for future research and clinical practice improvement.